2012
DOI: 10.1371/journal.pgen.1003071
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Global Pain Systems Network Highlights Phospholipid Signaling as a Regulator of Heat Nociception

Abstract: The ability to perceive noxious stimuli is critical for an animal's survival in the face of environmental danger, and thus pain perception is likely to be under stringent evolutionary pressure. Using a neuronal-specific RNAi knock-down strategy in adult Drosophila, we recently completed a genome-wide functional annotation of heat nociception that allowed us to identify α2δ3 as a novel pain gene. Here we report construction of an evolutionary-conserved, system-level, global molecular pain network map. Our syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
(56 reference statements)
3
18
0
Order By: Relevance
“…In the following years several papers reported a seemingly contradictory result: PI(4,5)P 2 in excised inside-out patches activated, rather than inhibited TRPV1 [49, 64, 109], raising doubts about PI(4,5)P 2 being inhibitory. Several other reports however were compatible with the existence of a partial inhibitory effect of PI(4,5)P 2 , present in intact cells [45, 64, 75, 83]. Most of the data in the literature had been consistent with a general dependence of TRPV1 activity on phosphoinositides, most likely via direct interactions of these lipids with the channel, and the possible presence of an indirect partial inhibition by PI(4,5)P 2 [29, 95].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…In the following years several papers reported a seemingly contradictory result: PI(4,5)P 2 in excised inside-out patches activated, rather than inhibited TRPV1 [49, 64, 109], raising doubts about PI(4,5)P 2 being inhibitory. Several other reports however were compatible with the existence of a partial inhibitory effect of PI(4,5)P 2 , present in intact cells [45, 64, 75, 83]. Most of the data in the literature had been consistent with a general dependence of TRPV1 activity on phosphoinositides, most likely via direct interactions of these lipids with the channel, and the possible presence of an indirect partial inhibition by PI(4,5)P 2 [29, 95].…”
Section: Introductionsupporting
confidence: 56%
“…Neely et al [75] found that PIP5K1α −/− mice had increased sensitivity to radiant heat and to capsaicin in behavioral assays. This finding is compatible with PI(4,5)P 2 exerting a negative effect.…”
Section: Evidence For Inhibition By Phosphoinositidesmentioning
confidence: 99%
“…The only GPCR-coupled PI3K, PI3Kγ, is expressed in nociceptive neurons and has been implicated in morphine-induced peripheral analgesia and tolerance [16; 42]. Surprisingly, PI3Kγ knockout ( Pik3cg −/− ) mice exhibit enhanced responses to heat and capsaicin, suggesting that PI3Kγ acts as a negative regulator of thermal and TRPV1 responses [60]. Interestingly, antagonism of this isozyme with a specific inhibitor in the periphery (via intraplantar injections) was shown to be anti-allodynic in a carrageenan-induced allodynia model [45].…”
Section: Lipid Kinases That Regulate Nociceptive Sensitizationmentioning
confidence: 99%
“…A recent functional genomics study identified phospholipid signaling and lipid kinases as key regulators of heat nociception in flies [60]. It was also found that PIP5KIα knockout ( Pip5k1a −/− ) mice displayed hypersensitivity to noxious heat and capsaicin but the precise underlying mechanism is unknown.…”
Section: Lipid Kinases That Regulate Nociceptive Sensitizationmentioning
confidence: 99%
“…At least one group has performed a small-scale in vivo double-knockdown screen [50]. In addition, a number of full-genome studies have been reported [33,5154]. Not all assay are dependent on transgenic RNAi; a large-scale screen in which dsRNA was injected into embryos, followed by time-lapse confocal microscopy, has also been reported [55].…”
Section: Drosophila In Vivo Screensmentioning
confidence: 99%